Keep My Teeth: An evaluation of multidisciplinary training in mouth care for people with intellectual developmental disorders. - Horan, Paul; Mac Giolla Phadraig, Caoimhin; Phelan, Sean (My University, 2024)
Aim: To evaluate a modular didactic training intervention called Keep My Teeth designed by special care dentists, for a range of healthcare students to provide oral homecare for people with intellectual developmental disorders (PwIDD). Methods: To evaluate the intervention a one-group pre-test post-test pre- experimental research design was utilized. The intervention was delivered by virtual platforms or face-to-face, with a sub-sample of participants also receiving practical training. Healthcare students included Speech and Language Ther- apy (SLT), Registered Nurse Intellectual Disability (RNID), Dental Science (DS), Dental Nursing (DN), and Dental Hygiene (DH). Results: Sixty-three of the 147 trainees completed all surveys. A significant change in perspective on barriers was seen for most groups post-training, with an increase in confidence in delivering oral care to PwIDD across disciplines; 67% of DH/DN students who took part in the practical training felt that the didactic training was just as effective without the practical training, while 42% of the DS students felt that was true. Conclusions: The training interventions provided seem to have increased the awareness of study participants in relation to barriers to care, and increased their self-efficacy towards, and intention to perform, oral homecare behaviors.
PUBLISHED
Keywords: health, intellectual developmental disorder, intervention, oral care, oral hygiene, training; Clinical learning environment in nursing; Intellectual Disability; Nursing Education; Intellectual Disability; Health